EXPLORATION OF WATTPAD APPLICATION AS A MEDIA FOR EFL STUDENTS IN READING CLASS - Mahmudah, Rifaatul; Daulay, Sholihatul Hamidah (TELL - US JOURNAL, 2023)
This study aimed for explore the Wattpad application for EFL reading classes. The types of research use a quantitative descriptive approach. The sampling technique of the study use purposive sampling. The participants of the study are thirty-seven undergraduate students and seven master’s degree (candidate lecturers) students in English Education at one of university of Medan, Indonesia. This study used the data collection is descriptive survey design use, which is survey about students’ and candidate lecturers’ (Master’s Degree) perspective on Wattpad in learning reading class. The researcher collected data of participants through an online questionnaire using Google form. Then analyse data used on the average number and the purpose of using the standard deviation is to reveal all the data related to the participant's question. Findings of the study in students’ responses about Wattpad as a learning medium is most students see Wattpad that is easiest reading platform because of accessible features such as reading features. Students’ responses about Wattpad tasted the Wattpad application is able and recognized that it is able to provide readers with information about things and issues that are happening around them so that it is interesting to discuss so it can support the student’s reading material in reading class. Students and candidate lecturers’ perspective on Wattpad in learning reading class is prospectively lecturers seeing Wattpad's potential as a medium in teaching reading. Whereas, based on candidate lecturers the Wattpad is useful for increasing student motivation in providing preferably involvement in achieving reading competence.